Usefulness of the SOFA score in the prediction of maternal death in the maternal ICU of the INMP - De la Peña Meniz, Walter J. (2020)
Objective:  To compare the SOFA score at admission and 24 hours and evaluate its usefulness in predicting maternal death. Materials and methods: A cross-sectional descriptive study of patients admitted to the Maternal ICU of the INMP was carried out from August 2014 to July 2019. Parametric and non-parametric tests were applied according to a previous evaluation of normality and a statistical significance p<0.05. Statistical analysis was performed using the statistical package STATA version 13. Results: The mean age corresponds to 28.32 years. The mean gestational age corresponded to 31.33 weeks; The mean hospital stay was 4.52 days. The area under the curve for SOFA at entry was 0.8818 and the area under the curve for SOFA at 24 hours was 0.9755.     P=0.1225. No significant differences were found between them. It was determined that the best cut-off point corresponds to a Score of 6 with a sensitivity that corresponds to 89.29% and a specificity of 79.13%. Conclusions: The SOFA Score adapts well to obstetric patients admitted to Maternal Intensive Care settings, maintaining a cut-off of 6 for admission SOFA with good sensitivity and specificity. (89.29%, 79.13%). The SOFA score is useful in maternal ICU environments and it should be used in our country.